2020
DOI: 10.1103/physrevfluids.5.073501
|View full text |Cite
|
Sign up to set email alerts
|

Generation of shear flows and vortices in rotating anelastic convection

Abstract: This is a repository copy of Generation of shear flows and vortices in rotating anelastic convection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…This is further supported in the review of Showman et al (2018), where it is stated that anelastic models provide similar flow features to the Boussinesq approach in the case of Saturn models. The very recent study of Currie & Tobias (2020), in a rotating plane layer, has shown that large coherent structures may be disrupted in the upper layers with the effect of stratification but, as concluded in Currie & Tobias (2020), it remains unclear whether the coherence is destroyed when the global Rossby number of the models is small, as is the case for our current models (see Table 1).…”
Section: Data Availabilitymentioning
confidence: 67%
“…This is further supported in the review of Showman et al (2018), where it is stated that anelastic models provide similar flow features to the Boussinesq approach in the case of Saturn models. The very recent study of Currie & Tobias (2020), in a rotating plane layer, has shown that large coherent structures may be disrupted in the upper layers with the effect of stratification but, as concluded in Currie & Tobias (2020), it remains unclear whether the coherence is destroyed when the global Rossby number of the models is small, as is the case for our current models (see Table 1).…”
Section: Data Availabilitymentioning
confidence: 67%
“…First, the heat fluxes used in these simulations (Chan, 2007;Käpylä et al, 2011) are larger than Jupiter's internal heat flux by several magnitudes. Second, in previous simulations on rapidly rotating convection only shear (Novi et al, 2019;Currie & Tobias, 2020) or large-scale cyclones (Chan & Mayr, 2013) can be found in low latitudes. The present study is motivated by the following questions.…”
Section: Introductionmentioning
confidence: 89%
“…First, the heat fluxes used in these simulations (Chan 2007;Käpylä et al 2011) are larger than Jupiter's internal heat flux by several magnitudes. Second, in previous simulations on rapidly rotating convection only shear (Novi et al 2019;Currie & Tobias 2020) or large-scale cyclones (Chan & Mayr 2013) can be found in low latitudes. The present study is motivated by the following questions.…”
Section: Introductionmentioning
confidence: 89%